Ethnomatematics Practices in The Traditional Funeral Rituals of The East Noemuti Community - Yohanis Ndapa Deda; Maria Krispina Tafin Nokas; Eduardus Beo Seo Delvion; Oktovianus Mamoh (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2026)
Traditional funeral rituals contain many mathematical concepts that have not been widely explored. Therefore, this study aims to investigate the mathematical activities contained in the traditional death rituals of the East Noemuti community. The study uses a qualitative, ethnographic approach. The research subjects included atoinamaf (uncles/traditional elders), bereaved families, and community leaders in Haekto Village, East Noemuti District, North Central Timor Regency. Data were collected through observation, interviews, and documentation, and then analyzed using Spradley's ethnographic analysis techniques, including domain analysis, taxonomy, component analysis, and cultural themes. The results of the study show that in the traditional death rituals of the Noemuti Timur community, there are various ethnomathematical activities, including: (1) tutu panu, which represents a hemispherical space; (2) making coffins and digging rectangular graves of a certain size; (3) nailing the coffin with three blows, symbolizing the concept of sacred numbers; (4) the use of circular silver coins as a symbol of spiritual provisions; and (5) the practice of calculating time in the tanono procession. The traditional death rituals of the East Noemuti community are spiritually and culturally meaningful, rich with mathematical concepts that can be used as a source of contextual learning.